Model of Environmental Education Affecting Green Consumption Behavior - Sutthiphapa, Nuntaporn (วารสารวิชาการมหาวิทยาลัยอีสเทิร์นเอเชีย ฉบับวิทยาศาสตร์และเทคโนโลยี (online), 2016)
The populations were 18,013 undergraduate students of Ubon Ratchathani Rajabhat University of the first semester of 2013. The Multi-Stage Random Sampling technique was used to collect the sample for 400 undergraduate students. The questionnaire was used as instrument for data collection. Structural Equation model (SEM) was used for model verification. The objective of research was to develop the causal relationship model of environmental education affecting green consumption behavior through inspiration of public consciousness. The results revealed that when considering on confirmatory factors of exogenous variable of Environmental Education (EE) was able to explain the variation of endogenous factors of Inspiration of Public Consciousness (IPC) to cause Green Consumption Behavior (GCB) with 98.00 percent. IPC was the most effect with 0.88 and subsequence was EE with the effect of 0.25. Additionally, confirmatory factors Environmental Education (EE) was able to explain the variation of confirmatory factors of Inspiration of Public Consciousness (IPC) with 87.00 percent.